An ERCOT test system for market design studies. (1st October 2020) - Battula, Swathi; Tesfatsion, Leigh; McDermott, Thomas E.
Highlights: Test system models centrally-managed wholesale power market and grid operations. Default settings for Texas energy region can easily be modified for other regions. Market and grid run for successive days with internally updated system conditions. User-set parameters permit flexible configuration of market and grid attributes. Reported 8-bus and 200-bus test cases demonstrate the test system's capabilities. Abstract: An open source test system is developed that permits the dynamic modeling of centrally-managed wholesale power markets operating over high-voltage transmission grids. In default mode, the test system models basic operations in the Electric Reliability Council of Texas (ERCOT): namely, centrally-managed day-ahead and real-time markets operating over successive days, with congestion handled by locational marginal pricing. These basic operational features characterize all seven U.S. energy regions organized as centrally-managed wholesale power markets. Modeled participants include dispatchable generators, load-serving entities, and non-dispatchable generation such as unfirmed wind and solar power. Users can configure a broad variety of parameters to study basic market and grid features under alternative system conditions. Users can also easily extend the test system's Java/Python software classes to study modified or newly envisioned market and grid features. Finally, the test system is integrated with a high-level simulation framework that permits it to function as a software component within larger systems, such as multi-country systems or integrated transmission and distribution systems. Detailed test cases with 8-bus and 200-bus transmission grids are reported to illustrate these test system capabilities.